PERBANDINGAN PENGUKURAN KADAR AIR TANAH LEMPUNG MENGGUNAKAN METODE GRAVIMETRY DAN METODE GYPSUM BLOCK BERDASARKAN VARIASI KEDALAMAN - Sir, Tri M. W.; Udiana, I Made; Isu, Sari R. (Jurnal Teknik Sipil, 2016)
Soil is one of the most important things in every civil engineering construction. But the problem is how to define physical and mechanic characteristic of the soil. Physical and mechanic characteristic that have influence on bearing capacity of the soil is water content. Size of soil also has effects on the changing of water content. To define water content, engineer is often using Gravimetry Method, but this method can only be doing in laboratory, so it can’t specifically describe real condition of water content in the fields. Then, an in-site test such as Electrical Sensory Method is needed, in order To get correct result of water content in fields. In Electrical Sensory Method there is one method called Gypsum Block Method, this method is an in-situ water content test with individual calibration on laboratory.The results from Oebelo Village, Kupang District soils sample, the soils is CH soil, where CH is organic clay with high plasticity, Fat Clay. By using gypsum block method, water content results is in range of 19,35 % - 41,05 %, while with gravimetry method the water content is in range of 18,34 % - 34, 67 %. Water content test using gypsum block method can only be doing at 0,50 m dan 1,00 m depth range, at 1,50 m dan 2,00 m depth range cannot be using this method because is too difficult to install gypsum block and the gap results between gravimetry method and gypsum block method is in range of 4,19 % - 7,69 %.